Cardiac surgery in solid organ transplant recipients: a clinical challenge - Farag, Mina; Nikolić, Marina; Weymann, Alexander (Expert review of cardiovascular therapy, 2017)
Due to continuous improvement of transplant medicine, the number of solid organ transplant recipients in need of cardiac surgery is constantly growing. The objective of this work was to compare different reports on outcomes in patients with previous solid organ transplant after cardiac surgery.
Gesehen am 27.11.2018